The links between religious coping and subjective well-being among Israeli-Muslims who lost a beloved person through death. Issue 4 (21st April 2021) - Abu-Raiya, Hisham; Jamal, Haneen
Abstract: This study examined the relationships between religious coping and indices of subjective well-being among 132 Israeli-Muslims who lost a beloved person through death. Participants provided demographic and death-related information, and completed measures of religious coping, satisfaction with life, positive/negative affect. Positive correlations were observed between positive religious coping and both satisfaction with life and positive affect, and between negative religious coping and negative affect. Further, the type of death (expected vs. sudden) was found to be a significant moderator between religious coping and subjective well-being. The theoretical and practical implications of the findings are discussed.